NFAT5-mediated expression of S100A4 contributes to proliferation and migration of renal carcinoma cells - Küper, Christoph; Beck, Franz-Xaver; Neuhofer, Wolfgang (Frontiers in Physiology, 2014)
The osmosensitive transcription factor nuclear factor of activated T-cells (NFAT) 5, also known as tonicity enhancer binding protein (TonEBP), has been associated with the development of a variety of tumor entities, among them breast cancer, colon carcinoma, and melanoma. The aim of the present study was to determine whether NFAT5 is also involved in the development of renal cell carcinoma (RCC). The most common type of RCC, the clear cell RCC, originates from the proximal convoluted tubule. We tested our hypothesis in the clear cell RCC cell line CaKi-1 and the non-cancerous proximal tubule cell line HK-2, as control. Basal expression of NFAT5 and NFAT5 activity in CaKi-1 cells was several times higher than in HK-2 cells. Osmotic stress induced an increased NFAT5 activity in both CaKi-1 and HK-2 cells, again with significantly higher activities in CaKi-1 cells. Analysis of NFAT5-regulating signaling pathways in CaKi-1 cells revealed that inhibition of the MAP kinases p38, c-Jun-terminal kinase (JNK) and extracellular regulated kinase (ERK) and of the focal adhesion kinase (FAK) partially blunted NFAT5 activity. FAK and ERK were both constitutively active, even under isotonic conditions, which may contribute to the high basal expression and activity of NFAT5 in CaKi-1 cells. In contrast, the MAP kinases p38 and JNK were inactive under isotonic conditions and became activated under osmotic stress conditions, indicating that p38 and JNK mediate upregulation of NFAT5 activity under these conditions. siRNA-mediated knockdown of NFAT5 in CaKi-1 cells reduced the expression of S100A4, a member of the S100 family of proteins, which promotes metastasis. Knockdown of NFAT5 was accompanied by a significant decrease in proliferation and migration activity. Taken together, our results indicate that NFAT5 induces S100A4 expression in CaKi-1 cells, thereby playing an important role in renal cell carcinoma proliferation and migration.